Algoritma Fisher-Yates sebagai Pengacak Soal pada Game Edukasi: Ruang Geometri - Finika, Alma Bryan Fitri; Andryana, Septi; Komalasari, Ratih Titi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
The perception of many students that mathematics is known to be difficult has made the experience negative, so that it has a general impact when adjusting to meeting material calculations. One of the basic materials of mathematics is geometry. This material has provided experiences for Elementary School (SD) children at grade 2 (two) to grade 4 (four). So, one solution is to play with Geometry Space. One of the android-based educational games that provides a media for self-adjustment in understanding material from Geometry. This study designed the Fisher-Yates algorithm in an educational game based on android which is named "Ruang Geometri". An algorithm that will help in randomizing the questions on the "Ruang Geometri" quiz. The purpose of this game is to change students' perceptions to be positive about mathematics because it is no longer a scary subject but fun. The results of this study are to recognize flat and space shapes in the form of educational games.
Keywords: Mathematic; Educational Game; Fisher-Yates Algorithm